Recovery of pressure and wave speed for photoacoustic imaging under a condition of relative uncertainty. (4th October 2019) - Acosta, Sebastián
Abstract: In this paper we study the photoacoustic tomography problem for which we seek to recover both the initial state of the pressure field and the wave speed of the medium from knowledge of a single boundary measurement. The goal is to propose practical assumptions to define a set of initial conditions and wave speeds over which uniqueness for this inverse problem is guaranteed. The main result of the paper is that given two sets of wave speeds and pressure profiles, they cannot produce the same acoustic measurements if the relative difference between the wave speeds is much smaller than the relative difference between the pressure profiles. Implications for iterative joint-reconstruction algorithms are discussed.